XIV International Conference on Graphic Expression applied to Building APEGA 2019. From the line to the point cloud (diségno, 2019)
The XIV International Congress of Graphic Expression applied to Building, promoted by the scientific association APEGA (Association of Teachers of Graphic Expression applied to Building) was held this year in Seville on 21, 22 and 23 February. (read more)